Extensional rheology and processing of polymeric materials - Münstedt, Helmut (International Polymer Processing, 2018)
Many processing operations of polymeric materials are dominated by extensional flow. In this paper the question is addressed in which way rheological data obtained from elongational laboratory experiments can be used to describe the material behavior in various processes. Particularly discussed is the uniformity of geometrical features of items with respect to the strain hardening of the polymeric materials, because uniformity is important for many end-use properties. Convincing correlations with extensional rheology could not be established for thermoforming experiments on polypropylene. However, for blown and drawn films it was found that the uniformity of thickness improved, if strain hardening was introduced. The bubble stability could be related to the melt strength of the sample. Furthermore, the influences of elasticity and strain hardening on the neck-in during drawing of films were elucidated. Moreover, it was shown in which way extensional rheology can be used to assess foaming.
Created from Fastlane, Scopus look-up